1995
DOI: 10.1080/0260293950200107
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the Value of Quality Assessment in Scottish Higher Education

Abstract: The 1992-93 session in Scottish universities saw the introduction of the Scottish Higher Education Funding Council's (SHEFC) statutory requirement to introduce quality assessments of teaching and learning. This paper looks at some of the issues that have arisen from the experience of staff at Napier University in terms of being assessed. It focuses on the issues that have arisen from the first and second round of visits to institutions. The key questions and problems associated with the process are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An evaluation of the first two rounds of the Scottish TQAs by Dickinson et al (1995) suggested that lead assessors had independently created``norms'' relating to the provision of teaching and learning, which were subsequently used as benchmarks against which universities' provision had been measured. These norms appeared to be subject-specific and unrelated to an individual university's aims and objectives.…”
Section: Introductionmentioning
confidence: 99%
“…An evaluation of the first two rounds of the Scottish TQAs by Dickinson et al (1995) suggested that lead assessors had independently created``norms'' relating to the provision of teaching and learning, which were subsequently used as benchmarks against which universities' provision had been measured. These norms appeared to be subject-specific and unrelated to an individual university's aims and objectives.…”
Section: Introductionmentioning
confidence: 99%
“…The 'doing something to'element of the education experience transformation process becomes a unique interaction involving both partiesvalue systems in making evaluative judgments of ongoing transactions. This in itself presents an unusual set of circumstances for as Dickson et al (1995) point out, "Education may be unique in the sense that it is difficult for the customer to assess the quality and relevance of the service. A university course is unusual in that the buyer, i. e. the student, may have only general ideas of what lies ahead and may not fully comprehend the content or relevance of a course until the later years of study or potentially long after graduation".…”
Section: Educational Transfonnation and Its Relevance To Value Systemsmentioning
confidence: 99%